2023
DOI: 10.3390/nano13061059
|View full text |Cite
|
Sign up to set email alerts
|

Single-Walled vs. Multi-Walled Carbon Nanotubes: Influence of Physico-Chemical Properties on Toxicogenomics Responses in Mouse Lungs

Abstract: Single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs) are nanomaterials with one or multiple layers of carbon sheets. While it is suggested that various properties influence their toxicity, the specific mechanisms are not completely known. This study was aimed to determine if single or multi-walled structures and surface functionalization influence pulmonary toxicity and to identify the underlying mechanisms of toxicity. Female C57BL/6J BomTac mice were exposed to a single dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 120 publications
1
6
0
Order By: Relevance
“…At Year 1, activation of some metabolic and biogenesis-related pathways was noted; however, activation of these pathways seems not to be specific to Year 1, but rather to be maintained until Year 2 (phospholipase and some nuclear receptor signaling pathways) ( Figure 10 ). Recently, impairment of pulmonary lipid homeostasis has been addressed in studies of the toxicities of electronic cigarettes and nanomaterials, including CNTs [ 22 , 52 , 53 , 54 , 55 ]. It was found that this could profoundly affect surfactant metabolism, lamellar body biogenesis in type II pneumocytes, and the plasticity and functions of alveolar macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At Year 1, activation of some metabolic and biogenesis-related pathways was noted; however, activation of these pathways seems not to be specific to Year 1, but rather to be maintained until Year 2 (phospholipase and some nuclear receptor signaling pathways) ( Figure 10 ). Recently, impairment of pulmonary lipid homeostasis has been addressed in studies of the toxicities of electronic cigarettes and nanomaterials, including CNTs [ 22 , 52 , 53 , 54 , 55 ]. It was found that this could profoundly affect surfactant metabolism, lamellar body biogenesis in type II pneumocytes, and the plasticity and functions of alveolar macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…At Year 2, several interesting canonical pathways were identified ( Figure 4 and Figure 10 ), many of which are not included in previous toxicogenomic reports analyzing CNTs ( Tables S8 and S9, and Figure S7 ) [ 16 , 17 , 18 , 22 , 24 , 38 , 39 , 40 , 41 , 42 ]. ERBB Signaling Pathway was significantly perturbed, but IPA analysis could not determine whether this pathway was upregulated or downregulated (z-score: −0.9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the contact impedance on the skin is several orders of magnitude higher than that of Ag/AgCl gel electrodes, leading to a unsatisfactory SNR. There is also concern about the toxicity of the nanofillers [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%